AUSTRALIAN MEDIA 9NEWS WEBSITE ARTICLES TENDENCY ON RUSSIA-UKRAINE WAR: A CRITICAL DISCOURSE ANALYSIS - Fatih, Muhammad Rajiv; Handayani, Tuty (Universitas Islam Negeri Sunan Gunung Djati, 2025)
Media challenges in presenting information are increasingly complex. Mass media sometimes fail to maintain the ethics of journalism, which require them to remain neutral. Large-scale events, such as the Russia-Ukraine war, trigger varying interests within particular social groups or even countries. However, Fairclough argued that there are several conditions under which the media become dependent on or affiliated with power holders or governments, as revealed in a specific branch of Critical Discourse Analysis. This research aims to examine how 9News uses certain language in conveying issues and managing the production and consumption of texts. It also analyzes the social practices created by the discourse of 9News, employing the concept of Media Discourse as a branch of Critical Discourse Analysis, as proposed by Fairclough. As a result, the research found that articles on the 9News website tend to discriminate against Russia and support Ukraine. This bias is influenced by ideology, which affects the delivery, production, and consumption of text. Consequently, the social practices produced by these texts result in injustice, revealing 9News' tendency on the issue.